Social media analytics for knowledge acquisition of market and non-market perceptions in the sharing economy. Issue 2 (13th June 2020) - Geissinger, Andrea; Laurell, Christofer; Öberg, Christina; Sandström, Christian; Sick, Nathalie; Suseno, Yuliani
Abstract : Purpose: Using the case of Foodora, this paper aims to assess the impact of technological innovation of an emerging actor in the sharing economy through stakeholders' perceptions in the market and non-market domains. Design/methodology/approach: Using a methodological approach called social media analytics (SMA) to explore the case of Foodora, 3, 250 user-generated contents in social media are systematically gathered, coded and analysed. Findings: The findings indicate that, while Foodora appears to be a viable provider in the marketplace, there is mounting public concern about the working conditions of its employees. In the market domain, Foodora manages its status as an online delivery platform and provider well, but at the same time, it struggles with its position in the non-market sphere, suggesting that the firm is vulnerable to regulatory change. These insights highlight the importance of simultaneously exploring and balancing market and non-market perceptions when assessing the impact of disruptive innovation. Originality/value: This study offers originality by providing an integrative approach to consider both the market and non-market domains. It is also novel in its use of SMA as a tool for knowledge acquisition and management to evaluate the impact of emerging technologies in the sharing economy.